A descriptive and validation study of a predictive model of severity of SARS-COV-2 infection - Villena-Ortiz Yolanda; Giralt Marina; Castellote-Bellés Laura; Lopez-Martínez Rosa M.; Martinez-Sanchez Luisa; García-Fernández Alba Estela; Ferrer-Costa Roser; Rodríguez-Frias Francisco; Casis Ernesto (Advances in Laboratory Medicine, 2021)
The strain the SARS-COV-2 pandemic is putting on hospitals requires that predictive values are identified for a rapid triage and management of patients at a higher risk of developing severe COVID-19. We developed and validated a prognostic model of COVID-19 severity.